The potential of chiroptical and vibrational spectroscopy of blood plasma for the discrimination between colon cancer patients and the control group - Tatarkovič, Michal; Miškovičová, Michaela; Šťovíčková, Lucie; Synytsya, Alla; Petruželka, Luboš; Setnička, Vladimír (Analyst, 2015)
Colorectal cancer is one of the most abundant causes of cancer deaths in the world. At an early stage, the established clinical procedures have low reliability and sensitivity. Therefore, we tested a novel approach based on chiroptical methods such as electronic circular dichroism (ECD) and Raman optical activity (ROA). These methods are suitable for detecting slight changes in the 3D structure of chiral biomolecules, some of which may be caused by pathological processes occurring during cancer growth. Fifty-five blood plasma samples were analyzed using the combination of ECD and ROA supplemented by conventional Raman and FT-IR spectroscopy. All obtained spectra were evaluated together by linear discriminant analysis. The accuracy of sample discrimination reached 100% and the subsequent leave-one-out cross-validation resulted in 93% sensitivity and 81% specificity. The achieved results indicate that chiroptical methods supplemented by Raman and FT-IR spectroscopy might be new supporting and minimally invasive tools in the clinical diagnosis of colon cancer.
Keywords: senioři; Spectrum Analysis, Raman; cirkulární dichroismus; senioři nad 80 let; Male; Middle Aged; mužské pohlaví; studie případů a kontrol; Adult; Aged, 80 and over; nádory tračníku; ženské pohlaví; Humans; Circular Dichroism; Colonic Neoplasms; lidé středního věku; dospělí; Female; Aged; Ramanova spektroskopie; lidé; Case-Control Studies